2008
DOI: 10.5194/bg-5-1425-2008
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneous ice nucleation activity of bacteria: new laboratory experiments at simulated cloud conditions

Abstract: The ice nucleation activities of five different Pseudomonas syringae, Pseudomonas viridiflava and Erwinia herbicola bacterial species and of Snomax™ were investigated in the temperature range between −5 and −15 • C. Water suspensions of these bacteria were directly sprayed into the cloud chamber of the AIDA facility of Forschungszentrum Karlsruhe at a temperature of −5.7 • C. At this temperature, about 1% of the Snomax™ cells induced immersion freezing of the spray droplets before the droplets evaporated in th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
129
1
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 132 publications
(135 citation statements)
references
References 22 publications
3
129
1
2
Order By: Relevance
“…Intact bacteria cells appear in the size range around 800 nm, visible as small bump in the size distribution. This is consistent with the size range in which bacteria cells for Snomax TM and P. syringae were found in Möhler et al (2008). The generated particles at sizes below the small bump are not made up of intact bacteria, but contain other Snomax TM ingredients such as e.g., cell constituents and nutrition remnants and also, as will later follow from our results, fragments of cell membrane with intact INA protein complexes.…”
Section: Snomax Tm and Particle Generationsupporting
confidence: 77%
See 3 more Smart Citations
“…Intact bacteria cells appear in the size range around 800 nm, visible as small bump in the size distribution. This is consistent with the size range in which bacteria cells for Snomax TM and P. syringae were found in Möhler et al (2008). The generated particles at sizes below the small bump are not made up of intact bacteria, but contain other Snomax TM ingredients such as e.g., cell constituents and nutrition remnants and also, as will later follow from our results, fragments of cell membrane with intact INA protein complexes.…”
Section: Snomax Tm and Particle Generationsupporting
confidence: 77%
“…The IN number size distribution shown in Fig. 6 is in contradiction to Möhler et al (2008) who speculated, based on polydisperse measurements, that only particles in the larger mode (D P ≥ 600 nm) of the bimodal size distribution are ice active. Results obtained in the study by Wood et al (2002) support our finding of INA protein complexes being present also in smaller size classes.…”
Section: Distribution Of Ina Protein Complexes Over Droplet Ensemblescontrasting
confidence: 46%
See 2 more Smart Citations
“…This statement is supported by field studies (DeMott et al, 2003b;Richardson et al, 2007;Klein et al, 2010) where high concentrations of mineral dust led to a significant increase in the ice crystal number concentration. Previous studies by Vali et al (1976); Schnell and Vali (1976); Möhler et al (2008) showed that bioaerosols and especially some specific bacteria like Pseudomonas Syringae initiate ice formation at warmer temperatures than mineral dust. Pratt et al (2009) found that one third of the ice particle residues in one cloud collected by a Counterflow Virtual Impactor (CVI) at high altitude over Wyoming contained biological markers.…”
Section: Introductionmentioning
confidence: 99%